Promotion effects of P and S for catalytic oxidation of methacrolein to methacrylic acid over heteroatoms doped carbon catalysts. (15th May 2023) - Zhou, Lilong; Zeng, Xiangjie; Qi, Miao; Li, Kunjie; Xu, Hong; Zhong, Yadong; Liu, Runjing; Yun, Jimmy
Graphical abstract: Highlights: A kind of efficient P and S co-doped carbon catalysts has been prepared by microwave carbonization method. P can depress the electrophilic groups and improve the selectivity of methacrylic acid. Doping of S in the carbon skeleton can increase the O2 adsorption sites, accelerate the redox process and improve the catalytic activity. Abstract: A series of phosphorus-sulfur co-doped porous carbon catalyst were prepared by microwave-assisted carbonization for selective oxidation of methacrolein (MAL) to Methacrylic acid (MAA). The physical and chemical properties of prepared carbon catalysts have been well characterized by various methods. Doped phosphorus atoms can transfer electrophilic groups to nucleophilic groups which can reduce the occurrence of side reactions. The CSC species produced by the introduction of sulfur atoms can make adjacent carbon atoms become O2 adsorption active sites, increasing the oxidation active sites, thereby increasing the activity of catalysts. The catalytic mechanism has been investigated by in situ DRIFTS. Prepared carbon catalysts exhibited excellent catalytic performance (over 50 % MAL conversion and 70 % MAA selectivity) and stability under gentle reaction conditions. This work shows a promise way to prepare efficient catalysts for gas–solid metal free catalysts for selective oxidation reactions and recovers the mechanism for improvement of catalytic activity by nonmetal atoms.